Development and preliminary evaluation of Chinese Vitiligo Quality of Life Scale (CVQLS) - Wang, Bo; Wang, Qi; Wang, Zeqian; Zhang, Jia; Zhou, Yuqi; Chen, Xiaoqi; Wu, Tong; Xiong, Shishi; Jin, Xiaodong; Gao, Shanshan; Shang, Lei; Li, Chunying; et al. (Frontiers in Psychology, 2025)
IntroductionCurrent research shows that there is no vitiligo quality-of-life measurement instrument suitable for Chinese patients. At present, the DLQI scale commonly used with vitiligo patients in China includes symptom dimensions or items that are not applicable to vitiligo patients. Therefore, it is necessary to develop a quality-of-life scale specific to vitiligo patients in China.MethodsIn this study, the item pool was created through a comprehensive review of relevant literature, focus group discussions, and brainstorming. Two rounds of Delphi expert consultation and a semi-structured interview were conducted to modify the item pool and form the draft scale. Two rounds of questionnaire investigations were used to select items and form the final scale. The reliability, validity, and discriminative ability were evaluated based on the third round of questionnaire investigation.ResultsThe scale contains 3 dimensions and 25 items, and the total cumulative variance contribution rate was 64.54%. The Cronbach’s α coefficient was 0.972; the split-half reliability coefficient was 0.950, and the test–retest reliability coefficient was 0.776. The Spearman correlation coefficient with the Dermatology Life Quality Index (DLQI) was 0.650. The scores of the scale or each dimension were correlated with patient characteristics, including gender, disease course, disease stage, Body Surface Area (BSA), and white spot area.ConclusionThis study developed the Chinese Vitiligo Quality of Life Scale (CVQLS) to measure the quality of life of vitiligo patients in China. Compared to the commonly used DLQI, the CVQLS removed items related to skin disease symptoms while incorporating concerns specific to Chinese patients, such as the economic burden. The scale is thus tailored to the needs of Chinese vitiligo patients. Preliminary results indicate that the CVQLS has good reliability, validity, and discriminative ability.